Essential georisk factors in the assessment of the influence of underground structures on neighboring facilities - Tomasz Godlewski; Eugeniusz Koda; Monika Mitew-Czajewska; Stanisław Łukasik; Simon Rabarijoely (Archives of Civil Engineering, 2023)
In civil engineering, underground structures are exposed to various georisks and require greater attention and awareness of the need to identify them at the earliest possible stage of investment preparation and implementation. The assessment of the interaction of objects in the underground space is a task that requires the analysis of many influencing factors resulting from the geometry and characteristics of the constructed structure and existing buildings, in the context of soil and water conditions. The correctness of such an assessment and forecast of the range and scope of these impacts requires knowledge of both construction and geotechnical issues, as well as knowledge of using the experience gained, including the analysis of the results of observations and monitoring measurements. One of the main challenges associated with underground constructions is their impact on existing buildings and other structures adjacent to the developed site. As these structures are often highly susceptible to excavation-induced ground movements, their behavior have to be considered in a design as one of the geotechnical-related limit states. As in the analysis of limit states, various computational models can be used to assess the impact of investments, including analytical, semi-empirical or numerical models. In the process of assessing the impact of underground structures, it is also important to identify additional elements of potential georisks, e.g. the impact of accompanying works, which in certain situations may have a significant impact on the construction process, requiring preventive measures. On a few examples from the construction of deep excavations and tunnels in different soil and water conditions, the article discusses the aspects of the role of the accuracy of the identification of soil and water conditions and the creation of a reliable and useful subsoil model as elements allowing for the identification and minimization of georisks and its proper management.